Tổng hợp, cấu trúc, hoạt tính kháng tế bào ung thư của hai phức chất platin(II) chứa metyleugenol và p-cloanilin - Huyền Tâm, Nguyễn Thị; Hương, Nguyễn Thị; Cẩm Mai, Trương Thị; Thanh Chi, Nguyễn Thị (Vietnam Journal of Chemistry, 2016)
Two organometallic complexes of platinum(II), [PtCl2(Meug)(p-ClC6H4NH2)] (M1) and [PtCl(Meug-1H)(p-ClC6H4NH2)] (M2) (Meug: methyleugenol), have been synthesized for the first time. The structures of M1 and M2 were determined by crystalline water, Pt analysis, EDX, IR, 1H NMR, 13C NMR and HSQC spectra studies. In these complexes, p-chloroaniline coordinates with the Pt(II) via N. In M1, Meug only coordinates with Pt(II) through C=C of the allyl group and the N atom occupies the trans-position in comparison to the allyl group. In M2, deprotonated Meug (Meug-1H) is bound up with platinum(II) both at ethylenic double bond of allyl group and at the C5 atom of benzene ring resulting in the cyclic complexe in which the N atom and the allyl group are cis positions to each other. M2 exhibits activity against MCF7 human cancer cell line with IC50 value of 92.23 μg/ml.